Terrestrial gamma radiation dose (TGRD) levels in northern zone of Bauchi, Nigeria: mapping and statistical relationship between gamma dose rates and geological formations (Gadau Journal of Pure and Allied Sciences, 2023)
This present study aims to obtain baseline data of environmental terrestrial radiation and to assess the corresponding health risk in the ambient environment in Bauchi north.  The Terrestrial gamma radiation dose rates (TGRD) of study area were measured on-site using a portable Radiation alert milli roentgen (mR) survey meter, with a total of 280 measured points which covered all geological formations of the study area. The TGRD ranged from 60.90 nGyh-1 to 313.20 nGyh-1 with a mean value of 165.48 nGyh-1, which is about two times higher than the world average value of 59 nGyh-1 . Geological formation (Granites) was found to have the highest mean TGRD value of 194.88 nGyh-1. Likewise, Geological formation (Quartenary sedimentary) appeared to have the lowest mean TGRD value of 151.82 nGyh-1. The map for the distribution and exposure rate due to TGRD for the study area was also plotted using Golden surfer 12 software. One-way ANOVA was used to investigate the variation of the significant difference between the geological formations with TGRD, which shows the influence of geological formation on the measured TGRD values of the study area. Measured data could further be used to evaluate the public radiation exposure and in formulating safety standards and radiological guidelines.
Keywords: Gamma dose rates; Annual effective dose; Geological formations; lifetime cancer risk; Contour map; Alpha particles; Beta particles; Health hazard; Ionizing radiations; Granites